PENGEMBANGAN APLIKASI TAMU WAJIB LAPOR DI DESA KARANGSALAM BATURADEN BERBASIS ANDROID - Saefudin Saefudin; Arif Dwi Saputra; Ragil Wijianto Ragil (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Information technology and its application devices are growing rapidly. Android-based technology is a technology that has been widely used in recent years, this is because Android supports the mobility of its users, only through smartphones can access various information as needed. Android is an operating system using Linux which is being developed in the midst of other OS. The application of android applications is not only carried out by large companies or agencies but can also be used in villages. Karangsalam Baturaden Village, Banyumas Regency, at the RT level has a guest system that is required to report 1x24 hours for security in the living environment, but many residents sometimes find it difficult and ignore this due to busyness and time constraints, as well as inefficiency when it comes to filling out forms and attaching files. such as photocopy of ID card. From these problems, it is necessary to solve the problem by making an Android-Based Application for Guest Visits in Karangsalam Baturaden Village. The method used is the Extime Programming method for system design and analysis, system description using flowcharts or flowcharts, data collection, namely observation and literature study, for making applications using the Kotlin programming language, Android Studio as an android-based application creation tool, for backend making APIs. using the php language, the database using PHPmyadmin. The guest application must report to facilitate the services of Karangsalam villagers at the RT level, especially when managing and monitoring visiting guests